1974
DOI: 10.1111/j.1365-2141.1974.tb00445.x
|View full text |Cite
|
Sign up to set email alerts
|

Leukaemic Reticuloendotheliosis (‘Hairy’ Cell Leukaemia): A Distinct Clinico‐Pathological Entity

Abstract: Summary. The main diagnostic features of leukaemic reticuloendotheliosis (LRE) are discussed in the light of six patients studied in recent years. A detailed study of the clinical, cytological, cytochemical and histological findings in four cases is presented. Pancytopenia and the presence of mononuclear ‘hairy’ cells in the circulation were the main haematological features. Bone marrow was difficult to aspirate and contained 50–80% of the same abnormal cells as the blood; the reticulin pattern showed increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
0
10

Year Published

1975
1975
2004
2004

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 170 publications
(44 citation statements)
references
References 38 publications
0
34
0
10
Order By: Relevance
“…Other studies confirmed the increase in the collagen fibrils in the intercellular space around the HCs but did not find evidence that HCs give rise to these fibrils (10). These studies also showed that HCs are not argyrophilic (29), suggesting that they may not be the direct source of reticulin fibers. Since no massive increase in fibroblast numbers is observed in the BM of HCL patients (10), the increased production of reticulin and ECM proteins might be due to an accelerated differentiation of fibroblasts into matrix-producing cells rather than to an increased proliferation.…”
Section: Introductionmentioning
confidence: 72%
“…Other studies confirmed the increase in the collagen fibrils in the intercellular space around the HCs but did not find evidence that HCs give rise to these fibrils (10). These studies also showed that HCs are not argyrophilic (29), suggesting that they may not be the direct source of reticulin fibers. Since no massive increase in fibroblast numbers is observed in the BM of HCL patients (10), the increased production of reticulin and ECM proteins might be due to an accelerated differentiation of fibroblasts into matrix-producing cells rather than to an increased proliferation.…”
Section: Introductionmentioning
confidence: 72%
“…Generally, they are considered as precursors of mature viruses [1]. Virus A particles are invariably present in murine tumor plasma cells but nei ther in normal murine nor in human plasmocytes [5,8,10]. The presence of virus-like particles in tumor plasma cells in a case of 'hairy cell' leu kemia is suggestive for a viral nature of this neoplastic disease.…”
Section: Discussionmentioning
confidence: 99%
“…Except for filopodia, 'hairy cells' do not show any constant morphological features typical for a specific cell type. 'Hairy cells' were supposed to be (a) abnormal lymphocytes [5,7]; (b) reticulum cells [3,9], or (c) histiocytes [2].…”
Section: Discussionmentioning
confidence: 99%
“…Blood buffy coat was obtained in four cases diagnosed by current clinical and morphological criteria (8,9). In our experimental conditions these abnormal nononuclear cells exhibited three main characteristics (Fig.…”
Section: Hairy Cell Leukemiamentioning
confidence: 99%